Factors of Using the Pedagogical Innovative Education Cluster in the Conditions of Modernized Education - R., Musurmonov; K. M., Xurramov; G. O., Saidqulova (European Journal of Life Safety and Stability (2660-9630), 2021)
The article discusses the advantages of using a pedagogical innovative education cluster in a modernized educational environment and the importance of using interactive pedagogical technologies in achieving educational effectiveness.